Comparison of the Concentration of Encephalitozoon cuniculi Genotypes I and III in Inflammatory Foci Under Experimental Conditions - Sak B; Holubová N; Květoňová D; Hlásková L; Tinavská J; Kicia M; Zajączkowska Ż; Kváč M (Dove Medical Press, 2022)
Bohumil Sak,1 Nikola Holubová,1 Dana Květoňová,1 Lenka Hlásková,1 Jana Tinavská,1,2 Marta Kicia,3 Żaneta Zajączkowska,3 Martin Kváč1,4 1Institute of Parasitology, Biology Centre, Czech Academy of Science, České Budějovice, Czech Republic; 2Faculty of Science, University of South Bohemia in České Budějovice, České Budějovice, Czech Republic; 3Department of Biology and Medical Parasitology, Wroclaw Medical University, Wroclaw, Poland; 4Faculty of Agriculture, University of South Bohemia in České Budějovice, České Budějovice, Czech RepublicCorrespondence: Bohumil Sak, Institute of Parasitology, Biology Centre, Czech Academy of Science, České Budějovice, Czech Republic, Tel +420387775421, Fax +420385310388, Email casio@paru.cas.czBackground: Microsporidia of the genus Encephalitozoon are usually associated with severe infections in immunodeficient hosts while, in immunocompetent ones, microsporidiosis produces minimal clinically apparent disease. Despite their microscopic size, microsporidia are capable of causing systemic infection within a few days. However, the mechanisms by which microsporidia reach target tissues during acute infection remain unclear. Out of four genotypes of Encephalitozoon cuniculi, only three are available for experimental studies, with E. cuniculi genotype II being the best characterized.Methods: In the present study, we tested the association between inflammation induction in immunocompetent and immunodeficient mice and the presence of spores of E. cuniculi genotypes I and III in selected organs using molecular methods and compared the results with previously published data on E. cuniculi genotype II.Results: We reported the positive connection between inflammation induction and the significant increase of E. cuniculi genotypes I and III occurrence in inflammatory foci in both immunocompetent BALB/c and immunodeficient severe combined immunodeficient (SCID) mice in the acute phase of infection. The induction of inflammation resulted in increased concentration of E. cuniculi of both genotypes in the site of inflammation, as previously reported for E. cuniculi genotype II. Moreover, our study extended the spectrum of differences among E. cuniculi genotypes by the variations in dispersal rate within host bodies after experimentally induced inflammation.Conclusion: The results imply possible involvement of immune cells serving as vehicles transporting E. cuniculi towards inflammation foci. The elucidation of possible connection with pro-inflammatory immune responses represents an important challenge with implications for human health and the development of therapeutic strategies.Keywords: Encephalitozoon cuniculi genotype I, Encephalitozoon cuniculi genotype III, inflammation, targeted migration